Tea as a functional food in preventive medicine from traditional Persian medicine point of view (a narrative review) (Iranian Society of Pharmacognosy, 2017)
Background and objectives: In recent years, phytomedicine has a main role to support immune system and in preventive medicine to decrease cancer incidence. Traditional medicine has a basic role to introduce herbal drugs to investigate in preventive medicine. Camellia Sinensis has two popular preparations, green (unfermented) and black (fully fermented) tea that among societies is beside water to drink. Methods: In this narrative review study, tea preparation as herbal infusions from traditional Persian available and reliable references beside classic herbal drugs references were studied to show benefits and risks of tea consumption in health. Results: Tea consumption is famous as antioxidative, anti-inflammatory, antimicrobial, anticarcinogenic, antihypertensive, neuroprotective. In traditional Persian medicine point of view its temperament is hot and dry so it can protect brain and stomach. It is sudatory and diuretic and can also increase mood. It is better to drink sweet or with milk to reduce its dryness. Conclusion: Tea preparations have a main role as a protective functional food in the human's lives.